A multi-trait approach identified 7 novel genes for back pain - Nadezhda M. Belonogova; Elizaveta E. Elgaeva; Irina V. Zorkoltseva; Anatoliy V. Kirichenko; Gulnara R. Svishcheva; Maxim B. Freidin; Frances M. K. Williams; Pradeep Suri; Tatiana I. Axenovich; Yakov A. Tsepilov (PAIN Reports)
Abstract. Introduction:. Back pain (BP) is a complex heritable trait with an estimated heritability of 40% to 60%. Less than half of this can be explained by known genetic variants identified in genome-wide association studies. Objectives:. We applied a powerful multi-trait and gene-based approach to association analysis of BP to identify novel genes associated with BP. Methods:. Using phenotypes and imputed genotypes from the UK Biobank 500k dataset, we generated a multi-trait phenotype by combining 3 BP-related phenotypes: chronic BP, dorsalgia, and intervertebral disk disorders. We performed gene-based association analysis for 3 BP-related phenotypes and multi-trait phenotype. Conditional analysis was applied to account for the effects of genetic variants outside the gene. Finally, we replicated significantly associated genes using the FinnGen database. Results:. We identified 32 genes associated with BP and replicated 16 of them. Thirteen genes were detected using the multi-trait phenotype. Seven of the detected genes, MIPOL1, PTPRC, RHOA, MAML3, JADE2, MLLT10, and RERG, were not previously reported. Several new genes are known to be associated with traits genetically correlated with BP or to be involved in pathways associated with BP. Conclusion:. Using new powerful methods of association analysis, we identified 7 novel genes associated with BP. Our results provide new insights into the genetics of back pain.